Ownership structure, income diversification, and banking resilience: Lessons from Indonesia’s financial sector - Kurniawati, Eris Tri; T, Sutrisno; Rahman, Aulia Fuad; Tojibussabirin, Muhammad (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of income diversification on bank performance, emphasizing the moderating role of ownership structure. Using panel data from Indonesian banks, we employ the Moderated Regression Analysis (MRA) to assess how ownership structure influences the relationship between diversification and financial performance. The findings indicate that income diversification does not significantly enhance bank profitability, particularly in state-owned banks, which remain reliant on traditional lending activities. In contrast, private and foreign-owned banks benefit more from diversified income sources, allowing them to achieve greater financial stability. Additionally, ownership structure moderates this relationship, weakening the positive effects of income diversification on bank performance. Further analysis highlights that liquidity, bank size, and capital adequacy contribute significantly to performance, while economic crises negatively impact profitability. These findings underscore structural challenges in state-owned banks and the need for regulatory frameworks that support more effective income diversification strategies. This study further highlights the importance of income diversification in enhancing bank resilience, particularly in response to economic crises and financial shocks. Future research should explore the role of financial technology and digital banking in improving diversification outcomes and reducing systemic financial risks.